Detection Efficiency of NaI(Tl) Detector in 511–1332 keV Energy Range - I. Akkurt; K. Gunoglu; S. S. Arda (Science and Technology of Nuclear Installations, 2014)
As it is important to obtain accurate analytical result in an experimental research, this required quality control of the experimental system. Gamma spectrometry system can be used in a variety of different fields such as radiation and medical physics. In this paper the absolute efficiency, peak to valley ratio, and energy resolution of a 3′′×3′′ NaI(Tl) detector were determined experimentally for 511, 662, 835, 1173, 1275, and 1332 keV photon energies obtained from 22Na, 54Mn, 60Co, and 137Cs radioactive sources.